Olfactory Dysfunction as a Biomarker for Early Diagnosis of Cognitive Impairment in Patients With Type 2 Diabetes: A Systematic Review - Paula Ramos-Cazorla; Lina Carazo-Barrios; Jose A. Reyes-Bueno; Elena Sagües-Sesé; Carmen de Rojas-Leal; Miguel A. Barbancho; Francisco J. Garzón-Maldonado; C. de la Cruz-Cosme; Juan A. García-Arnés; Natalia García-Casares (Journal of Diabetes Research)
Conclusions: Olfactory dysfunction could be a biomarker for early diagnosis of CI in T2DM. However, these alterations are highly heterogeneous and more studies that include neuroimaging need to be conducted.